Exploring the understanding and nature of parent-child communication on sexual and reproductive health: A qualitative study - Zilpah Saul Ombijah; Paschal Charles Mdukula; Benedicto Osward Luvanda; Egedius Kamanyi; Adedayo L. Abah (Health Literacy and Communication Open)
Background Adolescent pregnancy poses significant health risks, particularly in developing countries, where complications from childbearing are a leading cause of death for girls aged 15 to 19. Despite global efforts to ensure access to SRH services, many adolescents in sub-Saharan Africa engage in early sexual activity, without protection or contraceptives, contributing to unwanted pregnancies.Aims This study examines the knowledge gaps in SRH and the nature of communication between parents and adolescents, aiming to identify challenges and propose strategies to improve family-level communication on SRH issues.Methods This qualitative cross-sectional study was conducted in the Morogoro and Dodoma regions of Tanzania, areas with high teenage pregnancy rates. The study involved 52 participants who were purposefully sampled. Data were collected from Focus Group Discussions (FGDs) and in-depth interviews. Eight (8) FDGs with adolescents and young parents and four (4) in-depth interviews with parents were conducted. Data was manually transcribed and translated into English. Using thematic analysis, data were coded into main themes and sub-themes as per the research objectives.Results The data reveal that many participants have limited knowledge and a narrow perception of SRH. Some participants exclusively link SRH to pregnant women visiting health centres. Regarding the nature of communication, the data reveal a lack of open discussion, use of indirect warnings, reliance on traditional practices, and one-sided conversations as the nature of SRH at the family level. The findings reveal that both parents and adolescents have limited and gendered understanding of what SRH is and what it is not. This narrow understanding contributes to reactive approaches rather than proactive approaches to SRH matters within families. We further argue that integrating cultural norms, modern ways, and a more inclusive SRH programme can provide a balanced approach leading to successful SRH interventions.Conclusions SRH knowledge amongst parents and adolescents in Dodoma and Morogoro regions in Tanzania is limited. The nature of communication between parents and their children is one-sided, confrontational and relies on cultural practices.